Surface modification with polymers as a tool to functionalize fabrics, fabricate graded materials and design interface of composites - Albers, Rebecca Faggion (Universidade Federal de São Carlos, 2021)
Tailoring the properties of a material for a target application often depends on combining features of different components. To effectively arrange these components in a material, several methods have been developed to chemically modify surfaces, tuning its chemical composition, morphology and properties. Chemically modifying both organic and inorganic substrates enables the fabrication of coatings, the modification of scaffolds and the modulation of mechanical properties of composites. In this work, chemical functionalization through Atom Transfer Radical Polymerization (ATRP) was explored to fabricate coatings on SiOx substrates and cotton-based wound dressings; modifying scaffolds for the fabrication of 3D polymer-based graded materials; and designing the interface of polymer matrix composites. Conventional ATRP in solution is sensitive to oxygen and often requires lengthy deoxygenation processes of the polymerization mixture. When a zero-valent metal (Mt0) is introduced to the system in surface-initiated ATRP, it acts as a reducing agent, consuming oxygen from the polymerization mixture and enables the grafting of polymer brushes under ambient conditions. Zn0 was used as a reducing agent in Zn0 SI-ATRP to favor a cheap, fast and oxygen-tolerant fabrication of polymer brushes. Chemically different polymers were grafted from SiOx substrates using microliter volumes of polymerization mixture and the applicability of the process was demonstrated by grafting polymer brushes from cotton-based wound dressings. SI-ATRP is also a polymerization method in which the grafting density depends on the distance between the initiator and the reducing agent. Such feature enables the fabrication of materials with a gradient of chemical composition and morphology. A scaffold containing ATRP initiator in its structure was fabricated through free radical polymerization (FRP) of a high internal phase emulsion (HIPE) and functionalized through Cu0 SI-ATRP, yielding single and multiple polymer gradients. Poly(oligoethylene glycol methacrylate) (POEGMA) and poly(N-isopropylacrylamide) (PNIPAM) single gradients and poly(2-Hydroxyethyl methacrylate) PHEMA and POEGMA double gradients were fabricated and investigated through attenuated total refection Fourier-transform infrared spectroscopy (ATR-FTIR) and image analysis of scanning electron microscopy (SEM) images. Moreover, polymers with different functionalities were synthesized through ATRP for the interfacial design of polymer matrix composites. Chemical compatibility between matrix and reinforcing elements enhances mechanical properties of composites, however interfacial architecture also influences the mechanical response of the final material. Interfacial vulcanization between the exposed S of 2D-MoS2 and the polybutadiene block of polystyrene-block-polybutadiene-block-polystyrene (PSBS) leads to the formation of loop-chain entanglements at the interface of the composite. To investigate the transference of stress from the matrix to the reinforcing elements at the interface of such composites, controlled architecture polymers were synthesized through conventional ATRP in solution, grafted to 2D-MoS2 and used as reinforcing elements in PSBS matrix composites. Such composites with interfacial brushes and loops were cyclic tested in tensile mode and revealed how molecular events taking place at the interface during loading and unloading cycles impacts the mechanical performance of polymer matrix composites.
Modificação de superfície com polímeros como uma ferramenta para funcionalizar tecidos, fabricar materiais com gradiente e modular a interface de compósitos
Keywords: Modificação de superfície; ATRP; Surface modification; Atom transfer radical polymerization; Polimerização radicalar por transferência de átomo; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES